Molecular pathways and nutrigenomic review of insulin resistance development in gestational diabetes mellitus - Guevara-Ramírez, Patricia; Paz-Cruz, Elius; Cadena-Ullauri, Santiago; Ruiz-Pozo, Viviana A.; Tamayo-Trujillo, Rafael; Felix, Maria L.; Simancas-Racines, Daniel; Zambrano, Ana Karina (Frontiers in Nutrition, 2023)
Gestational diabetes mellitus is a condition marked by raised blood sugar levels and insulin resistance that usually occurs during the second or third trimester of pregnancy. According to the World Health Organization, hyperglycemia affects 16.9% of pregnancies worldwide. Dietary changes are the primarily alternative treatment for gestational diabetes mellitus. This paper aims to perform an exhaustive overview of the interaction between diet, gene expression, and the metabolic pathways related to insulin resistance. The intake of foods rich in carbohydrates can influence the gene expression of glycolysis, as well as foods rich in fat, can disrupt the beta-oxidation and ketogenesis pathways. Furthermore, vitamins and minerals are related to inflammatory processes regulated by the TLR4/NF-κB and one carbon metabolic pathways. We indicate that diet regulated gene expression of PPARα, NOS, CREB3L3, IRS, and CPT I, altering cellular physiological mechanisms and thus increasing or decreasing the risk of gestational diabetes. The alteration of gene expression can cause inflammation, inhibition of fatty acid transport, or on the contrary help in the modulation of ketogenesis, improve insulin sensitivity, attenuate the effects of glucotoxicity, and others. Therefore, it is critical to comprehend the metabolic changes of pregnant women with gestational diabetes mellitus, to determine nutrients that help in the prevention and treatment of insulin resistance and its long-term consequences.